INDEPENDENT EXTRACURRICULAR WORK OF STUDENTS-FOREIGNERS: VALUE, KINDS, ORGANIZATION, PROBLEMS - Личук, С. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the article the value of extracurricular independent work is reflected for students-foreigners, its kinds and advantages, and also problems of such activity and influence of it, high-quality organization on the increase of efficiency of preparation of specialists.